Effect of inhibition of Helicobacter pylori urease activity by acetohydroxamic acid on serum gastrin in duodenal ulcer subjects. Issue 8 (August 1991) - el Nujumi, A M; Dorrian, C A; Chittajallu, R S; Neithercut, W D; McColl, K E
Abstract : The mechanism of the hypergastrinaemia associated with Helicobacter pylori infection is unknown. It may be an effect of the ammonia produced by the bacterium near the antral epithelial surface. We have examined the effect on serum gastrin of inhibiting H pylori urease activity with acetohydroxamic acid in six duodenal ulcer patients. On day 1 the fasted patients received placebo tablets at 8 am, a peptide meal at 10 am, and a 14C urea breath test at 11.30 am. The next day 750 mg acetohydroxamic acid was administered orally in place of the placebo. The median (range) 30 minute breath test value (dose/mmol CO2 X kg body wt X 100) was 152 (111-335) on day 1, but only 22 (14-95) the next day (p less than 0.03). Further studies performed in one subject confirmed that acetohydroxamic acid lowered the ammonium concentration and raised the urea concentration in gastric juice. The inhibition of urease activity and ammonia production did not result in a fall in the basal gastrin concentration or in the median integrated gastrin response to the peptide meal, which was 78 ng/1.h (range 21-222) on day 1 and 79 ng/1.h (33-207) the next day. Ten days after acetohydroxamic acid, the urea breath test values were similar to those before treatment. This study shows that the raised gastrin concentration in patients with H pylori infection is not directly related to the organism's urease activity. It also shows that temporary suppression of H pylori urease activity does not clear the infection.